Vaccines for biodefense and emerging and neglected diseases - Barrett, A. D. T. (Alan D. T.); Stanberry, Lawrence R. (Academic, 2009)
The last 20 years has seen a rapid increase in infectious diseases, particularly those that are termed "emerging diseases" such as SARS, "neglected diseases" such as malaria and those that are deemed biothreats such as anthrax. It is well-recognized that the most effective modality for preventing infectious diseases is vaccination. This book provides researchers with a better understanding of what is currently known about these diseases, including whether there is a vaccine available or under development. It also informs them of what they need to do if they are currently working on developing a vaccine. * Provides a comprehensive treatise of the agents that are responsible for emerging and neglected diseases and those that can be used as biothreats * Includes the processes such as the vaccine development pathway, vaccine manufacturing and regulatory issues that are critical to the generation of these vaccines to the marketplace * Each chapter will include a map of the world showing where that particular disease is naturally found